2018
DOI: 10.1093/jn/nxx011
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Food Group Dietary Diversity Score Outperforms a 7-Food Group Score in Characterizing Seasonal Variability and Micronutrient Adequacy in Rural Zambian Children

Abstract: DDS-W performed better than DDS-IYCF in characterizing seasonal variability and micronutrient adequacy among rural Zambian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 23 publications
4
53
2
Order By: Relevance
“…I analyzed the dietary recall data by grouping each consumed ingredient into pre-set nutritional food groups (according to Caswell et al 25 ; Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…I analyzed the dietary recall data by grouping each consumed ingredient into pre-set nutritional food groups (according to Caswell et al 25 ; Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…MDD was developed to reflect adequacy of the micronutrient density of complementary foods of children aged six to 23 months, and thus is not appropriate to reflect the micronutrient adequacy of diets of children older than 23 months. A recent study showed that MDD-W performed better than MDD for predicting micronutrient adequacy among rural Zambian children 4 to 8 years of age (Caswell et al, 2018). Similarly, another recent study established that, using the MDD-W among pregnant women in Bangladesh, a cut-point of 6 or more food groups performed better than the cut-point of 5 or more food groups recommended for non-pregnant women (Nguyen et al, 2018).…”
Section: Age/sex Population Groups Not Represented In Standard Fgismentioning
confidence: 99%
“…In addition to the limits of relying on rain-fed production, poor market access, limited food processing activities that would extend the shelf-life of perishable goods (7,21), and high price fluctuations (20,21) further contribute to the seasonality of diets and consequently to varying levels of energy and nutrient intakes. Such seasonal dietary patterns have been commonly reported from other parts of rural Africa (24,25), and can have serious adverse effects, including insufficient weight gain during pregnancy and low birth weight of babies (26,27).…”
Section: Discussionmentioning
confidence: 93%